The Importance of Education in the Mother Tongue for Primary School - Rizgar Esmail Kareem; Sajida Abdullah Farhadi (QALAAI ZANIST JOURNAL, 2024)
Mother tongue is the child’s first language and the child receives and learns it from his parents and those who surround him. Indeed, it forms the structure of the child’s personality, identity and culture. Achieving that depends on the beginning of the primary school. So, it is important for children to start their primary education in their mother tongue. In contrast, depriving children of primary education has bad consequences. In that regard, this research discusses ‘The importance of education in the mother tongue for children in the primary school’, and employs the descriptive (analytical) method to present the consequences of education in the mother tongue. The research consists of three parts: the first part is the methodology of the research, and the second part explains the concepts and terms related to the research. Moreover, the third part discusses the importance of education in the mother tongue for children and the dangers of not doing so. Finally, the study sheds light on several important conclusions, with reference to the sources that are used.